[OP.5A.06] HIGH SALT DIET-INDUCED MICROVASCULAR DYSFUNCTION IS ASSOCIATED WITH REDUCED ANTIOXIDANT CAPACITY IN YOUNG HEALTHY WOMEN. (September 2016) - Stupin, A.; Cosic, A.; Rasic, L.; Seric, V.; Drenjancevic, I.
Abstract : Objective: Our previous study demonstrated that one week of high salt (HS) loading significantly impaired skin microvascular reactivity without changes in blood pressure (BP) levels. The aim of this study was to evaluate if this HS diet-induced microvascular dysfunction is associated with changes in antioxidant capacity in young healthy women. Design and method: Young healthy women (N = 33) were assigned to take HS diet (about 14 g of NaCl/day) for 7 days. BP and heart rate (HR) were measured before and after diet protocol. Post-occlusive reactive hyperemia (PORH) in the skin microcirculation was assessed by laser Doppler flowmetry (LDF). Plasma and 24 h-urine sodium were measured before and after diet protocol. Compliance to the prescribed diet was assessed by calculating salt intake from 24 h-urinary sodium excretion. As an idicator of antioxidant capacity, the ferric reducing ability of plasma - the FRAP assay with Trolox used as standard (mM Trolox) (spectrophotometric method) was detected before and after diet protocol. Results: There was no change in BP and HR before and after diet protocol. Changes in 24 h urinary sodium and calculated salt intake (salt intake/g before HSD 6.4 ± 2.6 vs. post HS diet 11.8 ± 5.9, P < 0.001) confirmed subjects conformed to the diet. HS diet caused significant impairment in PORH (R-O before HS diet 136 ± 49% vs. post HS diet 110 ± 29%, P = 0.017). One week of HS diet significantly reduced FRAP (antioxitant capacity) (FRAP mM/L before HS diet 0.68 ± 0.29 vs. after HS diet 0.61 ± 0.27, P = 0.019). We found positive correlation between R-O value (measure of PORH) and FRAP (antioxidant capacity) (r = 0.454, P < 0.001), while there was negative correlation between salt intake and FRAP (r = -0.262, P = 0, 031) just as between salt intake and R-O (r = -0.324, P = 0.007). Conclusions: This study confirmed our previous results that one week HS diet significantly altered microvascular reactivity in young healthy normotensive women, without changes in BP. Furthermore, our results have shown that HS diet significantly reduced antioxidant capacity which can be associated with microvascular dysfunction, since there is positive correlation between microvascular reactivity and FRAP assay in young healthy women.